Physical modelling in geotechnics - 6th ICPMG '06. proceedings of the sixth International Conference on Physical Modelling in Geotechnics--6th ICPMG '06, Hong Kong, 4-6 August 2006 /: proceedings of the sixth International Conference on Physical Modelling in Geotechnics--6th ICPMG '06, Hong Kong, 4-6 August 2006. Volume 1 : (2006) - Unknown
No abstract available